돼지의 웅취 호르몬과 성장 및 번식형질에 대한 유전모수추정 - 정종현; 정영철; 이상민; 강다래; 심관섭; 이중재; Jong-Hyun Jung; Young-Chul Jung; Sang-Min Lee; Da-Rae Kang; Kwan-Sub Shim; Jung-Jae Lee (농업생명과학연구, 2020)
웅취는 돼지고기의 이취로서 소비자의 소비성에 부정적인 영향을 미친다. 웅취는 거세를 하지 않은 수퇘지의 지방조직에 안드로스테 논, 스카톨 및 인돌과 같은 호르몬의 축적으로 인한 것이다. 본 연구는 웅취에 영향을 미치는 호르몬과 성장 및 번식 형질간의 유전상관도 를 추정하고 동물복지측면에서 웅취 호르몬이 낮은 수퇘지를 개발하기 위해 수행되었다. 본 연구를 위하여 3개 품종, Duroc, Landrace, Yorskhire 517두를 공시돈으로 수행하였다. 웅취 호르몬 분석을 위한 샘플채취는 수퇘지의 목부위 지방을 바이옵시 방식으로 채취하여 각 품종별 안드로스테논, 스카톨 및 인돌을 분석하였다. 안드로스테논 분석 결과, Duroc 품종이 1.684 ug/g으로 가장 높았고, 타 품종은 0.875-0.920 ug/g으로 상대적으로 낮았다. 스카톨의 농도는 Yorskhire가 0.095 ug/g으로 가장 높았고 인돌은 Duroc이 0.058 ug/g으로 가장 높았다. 품종과 개체에 따라서 3종류 웅취 호르몬의 농도 차이는 매우 컸다. 안드로스테논, 스카톨 및 인돌의 유전력은 0.40, 0.17 및 0.01으로, 안드로스테논의 유전력이 가장 높았다. 웅취 호르몬 농도와 다른 경제 형질(성장 및 번식 형질) 사이의 유전적 상관관계를 조사하였으나, 웅취 농도와의 상관관계는 매우 낮았다. 웅취 호르몬의 농도가 유전력도 높고 개체별 차이가 크고 다른 경제 형질과의 유전적 상관도가 낮기 때문에, 육종을 통한 저 웅취 부계 종돈 작출이 가능할 것으로 판단된다. Boar taints are showing negative effects on consumer’s preference of pork due to off-odor. The boar taint of pork caused by androstenone, skatole and indole hormones accumulated in adipose tissue of uncastrated male pigs. The purpose of this study was to estimate genetic parameters, to find possibility to breed low boar taint boars to replace castration procedure which currently performed at the swine farm. The fat tissues from neck of the live boars were sampled by biopsy process. Three breeds of boar were tested, they are Yorkshire, Landrace, and Duroc. Three boar hormones, androstenone, skatole and indole of each pig were analyzed. Duroc breed was the highest with 1.684 ug/g in androstenone, the others were relatively low with 0.875-0.920 ug/g. Skatole and indole concentrations were highest on Yorkshire and Duroc, respectively. The heritabilities of androstenone, skatole and indole were 0.40, 0.17 and 0.01, respectively. Andrestenone showed highest heritability among boar hormones. The genetic correlations between boar taint compounds and economic traits (growth and reproductive traits) were very low. It is considered that boar taint compounds could be possibly thorugh breeding, since heritabilities of boar taint hormones are high, and genetic correlations between the hormones and traits are low.